Assessment of Physical and Mechanical Properties of Polyurethane as Ground Improvement Material for Peat - Mohamad Niizar Abdurahman; Adnan Zainorabidin Kasbi Basri; Azman Kassim (NAROTAMA UNIVERSITY, Indonesia, 2021)
Peat is considered problematic soil due to its large void ratio, high compressibility and low shear strength. Various ground improvement methods have been developed in recent years to improve peat’s strength properties. Polyurethane grouting is one of the ground improvement methods that is gaining recognition as effective and fast way to stabilize soil. Polyurethane is a lightweight material produced by mixing polyol and isocyanate chemicals. Upon mixing, a polyurethane foam is created which expands up to a few times of its original volume. In this study, the strength characteristics of polyurethane with different mix ratios of polyol to isocyanate were evaluated to determine the optimum ratio suitable to be used to stabilize peat. Polyol to isocyanate ratio of 1:1, 1:1.5, 1:1.2, 1:2.5 and 1:3 were tested in this this research. The propagation, microstructure and density of polyurethane were investigated. Compressive strength of polyurethane determined using Unconfined Compression Strength test. Polyurethane created with higher ratio of isocyanate bears higher density and compressive strength compared to the polyurethane with lesser quantity of isocyanate. The cell structure of the polyurethane also is smaller with thicker cell walls. However, the curing time consumed by the polyurethane with high ratio of isocyanate is 8 times greater than the normal polyurethane. Thus, polyurethane ratio with fast curing time and high compressive strength was chosen as the optimum mix ratio to be used to stabilize peat.